IN MEMORY OF PROFESSOR V.G. BELIKOV - B. V. Borovsky; M. V. Larsky; O. O. Frolova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Article is devoted to basic life milestones of Professor, Doctor of Pharmacy, Honored Scientist of Russia V. G. Belikov, who made a great contribution to the development of domestic pharmaceutical education and science, more than 30 years headed the leading pharmaceutical institution of the country.